ANALISIS PUTUSAN PENGADILAN NEGERI GORONTALO NOMOR 209/PID.SUS/2021 BERKAITAN DENGAN TINDAK PIDANA NARKOTIKA YANG DILAKUKAN DENGAN PEMUFAKATAN JAHAT - Muhammad Rachmad Tahir; Maryam Baruadi (Fakultas Hukum Universitas Djuanda, 2023)
In providing health services, narcotics have an important role because they are used for medical and research purposes, so their availability needs to be guaranteed through production and import activities. Evil conspiracy is an act of preparation. Many law enforcement officers in Indonesia apply Article 132 paragraph 1. For example, two people have been arrested and charged for purchasing, carrying and subsequently using these narcotics. This research aims to analyze the judge's decision regarding criminal acts involving malicious conspiracy. The approach method uses primary data by conducting observations and interviews with related parties. Based on the facts, the author concludes: Narcotics crime with malicious intent because the defendant when committing the act was in good physical and mental health and there was no reason to expunge the crime and fulfilled the elements in Article 114 paragraph 2 of Law Number 35 of 2009 concerning Narcotics and Judges imposed a prison sentence of 8 years and a fine of IDR 2,000,000,000.00, with the provision that if the fine is not paid it will be replaced by a prison sentence of 3 months